Dynamics of household food security pre and post the COVID-19 pandemic in Bengkulu Province, Indonesia - Asriani, Putri Suci; Wibowo, Hariz Eko; Sukiyono, Ketut; Agusti, Netta (Publisher of Widyagama University of Malang (UWG Press), 2024)
After the COVID-19 pandemic, there have been changes in the Food Security Index in Bengkulu Province. One of the main challenges in supporting food security at the household level is the development of community capacity and self-reliance in addressing food issues. Information is needed factors that affect household food security in Bengkulu Province, including the impact of the COVID-19 pandemic. This research aims to analyze the factors thatÂ influencing household food security and understanding the dynamics before and after the COVID-19 pandemic regarding household food security in Bengkulu Province. This research can provide a basis for policy-making for the Government of Bengkulu Province. The analytical method used is multinomial logistic regression to identify the factors affecting household food security. The results of analysis show that influencing household food security include pre- and post-pandemic, home ownership status, lighting type, recipients of the Family Hope Program (PKH), adequate sanitation, and average household expenditure. There has been a decrease in energy consumption in self-owned households and households not receiving PKH after the COVID-19 pandemic. Significant changes also occurred in households with non-PLN lighting. Households with inadequate sanitation tend to be food insecure. The pandemic tends have a higher expenditures of household.JEL ClassificationÂ D19; H75; Q18